Brazil Land Governance Assessment - World Bank (Washington, DC, 2015)
This report on the assessment of land governance in Brazil summarizes and discusses the results of a series of standardized self-assessments of the land governance situation in Brazil, conducted entirely by Brazilian speakers. Therefore, these findings represent the perception of local experts based on their experience of news and data available. The main aim of this report are federal and state authorities directly involved in land governance in the evaluated states and other states. The general objective of the development of this assessment is to measure reliably the skills and the performance of land governance in a cross section of the country. This assessment is highly relevant and timely, as the land and real estate of natural resources linked to the land are the central core of the current competitiveness of Brazil and its strategically valuable position in the changing world economy. The evaluation methodology was the Assessment Framework of Land Governance (LGAF) developed by the World Bank. It focused on five key areas of good land governance and three additional topics. Key areas were: legal, institutional and associated policies to land rights; planning of land use and taxation; identification and ownership of land management of the state; provision of public land information; and dispute settlement. The optional modules used in some evaluations focused on the large-scale acquisition of land, forestry and the regularization of land tenure. Based on the LGAF in related workshops and review of some publications, the review has identified four areas of relative force on the Brazilian land governance. They include the guarantee of property rights, transparency in allocation of public land, public accessibility of information on registered land and transparency of increasing concern emerging from the influence of democratic and social movements. In addressing these and other areas of reform of land governance, the efforts of the newly created Inter-ministerial Working Group on Land Governance (IMWG) will be vital. That is particularly so because some of the reforms depend on the consistency of improving legal and institutional framework for land governance, which is necessarily a collaborative and cross-sector enterprise. This report therefore calls on the IMWG to join the Presidents Office to create an annual and transparent work program, for a period of at least three years with a regular mechanism of agreed reporting to the IMWG Office and Civil Office of the Presidency.